Atomic‐Level Design of Active Site on Two‐Dimensional MoS2 toward Efficient Hydrogen Evolution: Experiment, Theory, and Artificial Intelligence Modelling. (14th July 2022) - Sun, Chun; Wang, Longlu; Zhao, Weiwei; Xie, Lingbin; Wang, Jin; Li, Jianmin; Li, Bingxiang; Liu, Shujuan; Zhuang, Zechao; Zhao, Qiang
Abstract: Atom‐economic catalysts open a new era of computationally driven atomistic design of catalysts. Rationally manipulating the structures of the catalyst with atomic‐level precision would definitely play a significant role in the future chemical industry. Of particular concern, there are growing research concentrating on MoS2 as a typical representative of transition metal dichalcogenides for its great potential of diverse atomic‐level reactive sites for applications in catalysis for hydrogen evolution reaction. At present, the rational design of MoS2 ‐based catalysts greatly depends on the comprehensive understanding of its structure–activity relationships of active sites that still lacks the systematic summary. In this regard, we dissected the internal relationships between diverse active‐site configurations of MoS2 and the corresponding catalytic activity theoretically and experimentally to give impetus to the design of next‐generation high‐performance MoS2 ‐based catalysts. The necessity of normalizing the existing activity evaluation methodology and developing more‐precise metrics is discussed. Moreover, the advancement of artificial intelligence as an effective tool for the research on physicochemical properties of catalysts as well as its important role in theoretical pre‐design has also been reviewed. Finally, we summarized the opportunities and challenges of the design of nanoscale catalysts with desired physicochemical properties by assembling atoms in a controllable way. Abstract : The rational design of catalysts at the atomic level opens a new era for the research on next‐generation high‐performance catalysts. With an emphasis on the structure‐activity relationships of diverse existing and promising active sites, the progress in the design of MoS2 ‐based catalysts from the aspects of the experiment, theory, and AI modeling are systematically discussed.